Intermittent oral levetiracetam reduced recurrence of febrile seizure accompanied with epileptiform discharge: a pilot study - Lin-Yan Hu; Xiu-Yu Shi; Hui Li; Meng-Na Zhang; Shu-Fang Ma; Li-Ping Zou (BMC, 2018)
Abstract Background In previous study, we have found intermittent oral levetiracetam (LEV) can effectively prevent recurrence of febrile seizure (FS). This study aimed to analyze the effects of the preventive on the patients with frequent FS accompanied with epileptiform discharge. Methods Patients with frequent FS were assigned to undergo Electroencephalogram (EEG). At the onset of fever, the patients who presented epileptiform discharge were orally administered with LEV with a dose of 15-30 mg/kg per day twice daily for 1 week, thereafter, the dosage was gradually reduced until totally discontinued in the second week. The seizure frequency associated with febrile events and FS recurrence rate during a 48-week follow-up were analyzed. Results among the 19 patients presented epileptiform discharge on EEG, 31.58% (6 of 19) had complex FS, 68.42% (13 of 19) had simple FS. Up to 57.89% (11 of 19) had a family history of seizure disorder and 36.84% (7 of 19) had a family history of FS in first-degree relatives. 42.11% (8 of 19) happened the first FS episode at the age < 18 months. 36.84% (7/19) presented generalized spikes, 63.16% (12/19) showed focal spikes. During the 48-week follow-up period, the patients experienced 26 febrile episodes, none of them presented seizure recurrence. Conclusion Intermittent oral LEV can prevent the seizure recurrence of FS accompanied with epileptiform discharge in 48-week. However, further randomized controlled trials should be conducted. Trial registration ChiCTR-IPR-15007241; Registered 1 January 2014 - Retrospectively registered.